2022
DOI: 10.31219/osf.io/tfyxa
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Testing a locus coeruleus-norepinephrine account of working memory, attention control, and fluid intelligence

Abstract: The current set of studies examined the relations among working memory capacity, attention control, fluid intelligence, and pupillary correlates of tonic arousal regulation and phasic responsiveness in a combined sample of over 1,000 participants in two different age ranges (young adults and adolescents). Each study was designed to test predictions made by two recent theories regarding the role of the locus coeruleus-norepinephrine (LC-NE) system in determining individual differences in cognitive ability. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 91 publications
0
5
0
Order By: Relevance
“…Several studies reported a correlation between pupil dilation and alpha suppression during aversive learning and resting state, suggesting a contribution of the LC‐NE system in alpha suppression (Dahl et al, 2022; Sharon et al, 2021). Individual differences in WM capacity and attention control have been hypothesized to be driven by the differences in NE expression supporting activity in the fronto‐parietal network, which is implicated in cognitive control (Robison et al, 2022; Unsworth & Robison, 2017). Similarly, others identified a link between pupil size and theta activity in cognitive control tasks (Dippel et al, 2017; Lin et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies reported a correlation between pupil dilation and alpha suppression during aversive learning and resting state, suggesting a contribution of the LC‐NE system in alpha suppression (Dahl et al, 2022; Sharon et al, 2021). Individual differences in WM capacity and attention control have been hypothesized to be driven by the differences in NE expression supporting activity in the fronto‐parietal network, which is implicated in cognitive control (Robison et al, 2022; Unsworth & Robison, 2017). Similarly, others identified a link between pupil size and theta activity in cognitive control tasks (Dippel et al, 2017; Lin et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies reported a correlation between pupil dilation and alpha suppression during aversive learning and resting state, suggesting a contribution of LC-NE system in alpha suppression (Dahl et al, 2022; Sharon et al, 2021). Individual differences in WM capacity and attention control have been hypothesized to be driven by the differences in NE expression supporting activity in the fronto-parietal network, that is implicated in cognitive control (Robison et al, 2022; Unsworth & Robison, 2017). Similarly, others identified a link between pupil size and theta activity in cognitive control tasks (Dippel et al, 2017; Lin et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…While the depth of encoding is indexed by pupil orienting constrictions and baseline pupil size (Galeano‐Keiner et al, 2023; Koevoet, Naber, et al, 2023), the maintenance of material is reflected by pupillary dilations (Beatty, 1982; Kahneman, 1973; Robison & Unsworth, 2019; Strauch, Wang, et al, 2022; Zhou et al, 2022). The prioritization of material is also accompanied by a pupil dilation response (Robison et al, 2023; Unsworth & Robison, 2018), but the direct link to behavior remains to be investigated. Beyond these more general pupil responses, the PLR provides even more finely grained item‐specific insights into VWM operations.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond the insights that the PLR provides into the internal prioritization process (Hustá et al, 2019; Unsworth & Robison, 2017c; Zokaei et al, 2019), prioritizing material in VWM also evokes an effort/alerting related dilatory pupil response more generally (Figure 1; Robison et al, 2023; Unsworth & Robison, 2018)—likely mediated by phasic LC firing as during pupil dilations during maintenance. We speculate that not only the extent of the prioritization‐evoked PLR is linked to performance (Zokaei et al, 2019), but that this more general dilatory response also predicts subsequent behavior in terms of accuracy, speed and precision.…”
Section: Prioritizationmentioning
confidence: 99%
See 1 more Smart Citation